High courts and social media in Latin America - Mariana Llanos; Cordula Tibi Weber (German Institute of Global and Area Studies (GIGA), 2021)
This article presents the first comparative evaluation of the social media presence of 17 Latin American high courts. We explore the intensity with which they use Twitter, Facebook, and YouTube, as well as the level of influence that each court has developed on these platforms. The resulting classification of courts shows how their performances differ: the most influential courts are not necessarily the most active; rather, they make a differentiated use of social media. The least influential courts show great dispersion around their respective levels of activity. Additionally, we present a preliminarily evaluation of the relationship between the level of trust in the judiciaries and the courts' presence on social media. We see that courts with higher levels of distrust are moderately more active and tend to have less influence. Two motivations could explain the court behaviour in social media: the pursuit of strategic self-promotion, and an ideal of institutional transparency.
Keywords: 300; constitutional courts; supreme courts; institutional legitimacy; social media; Latin America